Potential Cardiovascular Risks Associated with Naltrexone-Bupropion Treatment in Overweight Patients [Response to Letter] - Lyu YS; Ahn H; Hong S; Park CY (Drug Design, Development and Therapy)
Young Sang Lyu,1 Hongyup Ahn,2 Sangmo Hong,3 Cheol-Young Park4 1Division of Endocrinology and Metabolism, Department of Internal Medicine, Chosun University Hospital, Gwangju, Republic of Korea; 2Department of Statistics, Dongguk University, Seoul, Republic of Korea; 3Department of Internal Medicine, Hanyang University Guri Hospital, Hanyang University College of Medicine, Guri, Republic of Korea; 4Department of Internal Medicine, Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, Seoul, Republic of KoreaCorrespondence: Cheol-Young Park, Division of Endocrinology and Metabolism, Department of Internal Medicine, Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, 29 Saemunan-ro, Jongno-gu, Seoul, 03181, Republic of Korea, Email cydoctor@skku.edu